Orthopaedic Snafus: When Adverse Events Happen in Orthopaedics. (March 2017) - Smith, Mary Atkinson; Walsh, Colleen; Levin, Barbara; Eaten, Kathyrn; Yager, Melissa
Abstract : The potential for adverse events exists when treating and managing orthopaedic patients in the intraoperative or postoperative environments, especially when it comes to falls, surgical site infections, venous thromboembolism, and injuries to nerves and blood vessels. Orthopaedic nurses play a vital role in the promotion and use of evidence-based interventions to decrease the incidence of these adverse events, improve quality of care, and minimize the financial burden related to these adverse events.